KSrAl3B2O9 crystal, growth method and application
Optimizing the growth conditions of KSrAl3B2O9 crystals by hydrothermal method, the problems of small crystal size and unstable mass in the prior art are solved, and the preparation of high purity, stability and large-size crystals are achieved, which are suitable for applications in the fields of optical and nonlinear optics.
Patent Information
- Application Number
- CN202411916793.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, KSrAl3B2O9 crystals have problems with small size, unstable mass and phase change during cooling during growth, which limits its further promotion in practical applications.
The KSrAl3B2O9 crystal was prepared by hydrothermal method. By optimizing raw material ratio and solvent selection, the effective growth of the crystal is achieved. The reaction conditions are mild, the product purity is high, the crystal growth is controllable, and the crystal size is large.
The crystal is achieved with high purity and stability, the crystal size can reach centimeters, with excellent optical properties and birefringence properties, and is suitable for optical devices and nonlinear optical effects applications.
Smart Images

Figure HDA0005207003360000011 
Figure HDA0005207003360000021 
Figure HDA0005207003360000022
Abstract
Description
Technical Field
[0001] The present invention relates to the field of crystal material synthesis, and in particular to a KSrAl3B2O9 crystal, a growth method and an application thereof. Background Art
[0002] As an important optoelectronic functional material, ultraviolet birefringent crystals have shown broad application prospects and important research value in the fields of optics and electronics. This type of crystal has a unique property: when light waves are projected onto its interface, two refracted light rays are generated due to the anisotropy of the material. This phenomenon is called birefringence. In particular, ultraviolet birefringent crystals show a significant birefringence effect in the ultraviolet spectrum.
[0003] At present, there are many types of known ultraviolet birefringent crystals, among which α-BBO (α-BaB2O4, barium borate) and MgF2 crystals are more typical representatives. α-BBO crystals have been widely used in high-power laser systems in the near-infrared, visible and ultraviolet bands due to their large birefringence, high laser damage threshold and wide transmittance range. However, α-BBO crystals are prone to phase change during growth, and the α phase turns into the β phase at about 925°C, causing the crystal to lose transparency and break. Although the α phase can be stabilized by ion doping, the growth complexity and cost are increased. In contrast, MgF2 crystals exhibit good birefringence properties in the deep ultraviolet region, but their birefringence is relatively small (about 0.01), which to a certain extent limits their efficient use, especially in application scenarios requiring large beam splitting angles.
[0004] In order to solve these problems, researchers are constantly exploring and developing new ultraviolet birefringent crystal materials. Among them, KSrAl3B2O9 crystal, as a crystal material with excellent optical properties, has shown potential application value in optical devices and nonlinear optical effects. However, the current growth method of KSrAl3B2O9 crystals uses KF as a flux, and the obtained crystals are small in size, unstable in quality, and there is a phase change during the cooling process, which limits its further promotion in practical applications. Therefore, it is of great significance to develop a method that can grow large-sized, high-quality KSrAl3B2O9 crystals, which is also an important direction for future scientific research. Summary of the invention
[0005] The present invention aims at the above-mentioned technical problems existing in the prior art and provides a method for preparing KSrAl3B2O9 crystals by a hydrothermal method. The method uses potassium carbonate, strontium oxalate, aluminum acetylacetonate and triethylboron as raw materials, acetic acid and ethanol as solvents, and realizes effective growth of crystals by optimizing the raw material ratio and solvent selection. The method has the advantages of mild reaction conditions, high product purity, controllable crystal growth, large crystal size, etc., thereby improving the performance of the crystals.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] On the one hand, the present invention provides a method for growing KSrAl3B2O9 crystals, which specifically comprises the following steps:
[0008] Step 1: Weigh potassium carbonate (K2CO3), strontium oxalate (SrC2O4), aluminum acetylacetonate (AlC 15 H 21 O6) and triethylborane (C6H 15 B), the molar ratio of potassium carbonate: strontium oxalate: aluminum acetylacetonate: triethylboron = 0.015: 0.025-0.035: 0.08-0.10: 0.07-0.11;
[0009] Step 2: Measure acetic acid solution, ethanol, and deionized water, mix them evenly and set aside, the volume ratio is acetic acid solution: ethanol: deionized water = 1:2:1, wherein the molar volume ratio (mol:ml) of potassium carbonate and acetic acid solution is 0.015:20;
[0010] Step 3: Add the raw materials weighed in step 1 to the solvent prepared in step 2, heat to 70-90° C. and stir to form a suspension solution;
[0011] Step 4: Transfer the solution obtained in step 3 to a hydrothermal reactor, seal it, and keep it at 190-210°C for 36-52 hours, then cool it to 190-110°C;
[0012] Step 5: After the reaction is completed, take out the reactor and cool it to room temperature, open the reactor, filter, wash and dry the reaction product to obtain the target crystal KSrAl3B2O9.
[0013] In a further improvement of the present scheme, the purity of the raw materials potassium carbonate, strontium oxalate, aluminum acetylacetonate and triethyl boron are all greater than 4N.
[0014] A further improvement of this scheme is that in step 2, 3.5% acetic acid solution and ethanol anhydrous ethanol solution are used.
[0015] A further improvement of this solution is that the stirring time in step three is 20-40 minutes.
[0016] A further improvement of this solution is that the cooling rate in step 4 is maintained at 0.3-0.7°C / h.
[0017] In a further improvement of this solution, in step 5, the drying temperature is 65-90° C. and the drying time is 10-13 hours. In a further improvement of this solution, in step 1, the molar ratio is potassium carbonate: strontium oxalate: aluminum acetylacetonate: triethylboron = 0.015: 0.03: 0.09: 0.09.
[0018] A further improvement of this scheme, the growth method of KSrAl3B2O9 crystal specifically comprises the following steps:
[0019] Step 1: weigh 0.015 mol potassium carbonate, 0.015 mol strontium oxalate, 0.09 mol aluminum acetylacetonate and 0.09 mol triethylboron, all raw materials having a purity greater than 4N;
[0020] Step 2: Measure 20 mL of 3.5% acetic acid solution, 40 mL of ethanol, and 20 mL of deionized water, mix well and set aside;
[0021] Step 3: Add the raw materials weighed in step 1 to the solvent prepared in step 2, heat to 80°C and continue stirring for 30 minutes to form a suspension solution;
[0022] Step 4: Transfer the solution obtained in step 3 to a 150 mL hydrothermal reactor, seal it and keep it at 200 °C for 44 hours, then slowly cool it to 100 °C at a cooling rate of 5 °C / h;
[0023] Step 5: After the reaction is completed, the reactor is taken out and cooled to room temperature, the reactor is opened, the reaction product is filtered, and washed with deionized water three times to remove residual solvent and impurities, and then dried at 80°C for 12 hours to obtain the target crystal KSrAl3B2O9.
[0024] On the other hand, the present invention provides a KSrAl3B2O9 crystal obtained by the above growth method.
[0025] In addition, the present invention provides the application of the above-mentioned KSrAl3B2O9 crystal in the field of ultraviolet birefringence optics.
[0026] Compared with the prior art, the advantages and positive effects of the present invention are:
[0027] (1) The present invention adopts a hydrothermal method to prepare KSrAl3B2O9 crystals, which has significant advantages and broad application prospects. Specifically, the method achieves effective crystal growth by precisely controlling the raw material ratio, solution concentration and reaction conditions, and prepares crystals with high purity and stable performance. The crystal lattice integrity is very good, and the crystal size can reach the centimeter level, which has extremely high application value.
[0028] (2) This method has mild reaction conditions, is easy to control, and is simple to operate with low energy consumption, which is conducive to obtaining high-quality crystals, reducing production costs and difficulties, and facilitating transformation and promotion. In addition, by selecting appropriate solvents and reaction conditions, the growth rate and morphology of the crystals can be further optimized, and the purity and yield of the product can be improved.
[0029] (3) The KSrAl3B2O9 crystal obtained by the present invention has stable and excellent transmission efficiency and birefringence performance, and exhibits good birefringence performance in the deep ultraviolet region.
[0030] (4) The method of the present invention has readily available raw materials, simple process, is green and environmentally friendly and conforms to the concept of sustainable development. It is not only suitable for laboratory research, but also suitable for large-scale industrial production, and has high industrial application value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The pictures of KSrAl3B2O9 crystals grown in Examples 1, 2 and 3 of the present invention;
[0032] Figure 2 The X-ray powder diffraction pattern of the KSrAl3B2O9 crystal obtained in Example 2 of the present invention;
[0033] Figure 3 The rocking curve of the (400) crystal plane of the KSrAl3B2O9 crystal obtained in Example 2 of the present invention;
[0034] Figure 4 This is the transmission spectrum of the KSrAl3B2O9 crystal obtained in Example 2 of the present invention;
[0035] Figure 5 This is the birefringence spectrum of the KSrAl3B2O9 crystal obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] To ensure the accuracy and reliability of subsequent experiments or production, the raw materials must be prepared according to the following molar amount and purity standards: 0.015 mol of potassium carbonate (K2CO3), with a purity of not less than 4N (99.99%); 0.025 mol of strontium oxalate (SrC2O4), with a purity of more than 4N; aluminum acetylacetonate (AlC 15 H21 O6) 0.09 mol, purity at least 4N; triethylborane (C6H 15 B) 0.07 mol, and the lower limit of the ratio is also selected to ensure that the purity exceeds 4N.
[0039] Measure 20 mL of 3.5% acetic acid solution, 40 mL of anhydrous ethanol and 20 mL of deionized water, mix well and set aside.
[0040] The weighed raw materials were added to the prepared solvent in sequence, heated to 80° C. and stirred for 30 minutes until a uniform suspension solution was formed.
[0041] The obtained suspension solution was transferred to a 150 mL hydrothermal reactor, sealed and kept at 200° C. for 36 hours, and then slowly cooled to 100° C. at a cooling rate of 0.3° C. / h.
[0042] After the reaction was completed, the reactor was taken out and cooled to room temperature. The reactor was opened, the reaction product was filtered, and washed with deionized water three times to remove the residual solvent and impurities. Subsequently, it was dried at 80°C for 12 hours to obtain the target crystal KSrAl3B2O9.
[0043] Figure 1 -(1) shows the crystal grown in Example 1. The crystal size is 5 mm. The crystal is colorless and transparent and has high quality.
[0044] Example 2
[0045] 1) Weigh 0.015 mol potassium carbonate (K2CO3), 0.03 mol strontium oxalate (SrC2O4), 0.09 mol aluminum acetylacetonate (AlC 15 H 21 O6) and 0.09 mol triethylborane (C6H 15 B), and grind and mix uniformly, and the purity of all raw materials is greater than 4N (i.e. 99.99%);
[0046] 2) Take the following solvents and mix them well for later use: 3.5% acetic acid solution: 20 mL, ethanol: 40 mL, deionized water: 20 mL;
[0047] 3) adding the raw materials weighed in step 1 to the solvent prepared in step 2 in sequence, heating to 80° C. and stirring continuously for 30 minutes until a uniform suspension solution is formed;
[0048] 4) Transfer the suspension solution obtained in step 3 to a 150 mL hydrothermal reactor, seal it and place it in a heating device. Keep it at 200°C for 44 hours to ensure that the reaction is fully carried out. Then, slowly cool it to 100°C, and the cooling rate is maintained at 0.5°C / h;
[0049] 5) After the reaction is completed, the reactor is taken out and cooled naturally to room temperature. The reactor is opened, the reaction product is filtered, and washed with deionized water three times to remove residual solvent and impurities. Subsequently, it is dried at 80°C for 12 hours to obtain the target crystal KSrAl3B2O9.
[0050] Figure 1 -(2) shows the crystal grown in Example 2. The crystal size is 11 mm. The crystal is colorless and transparent and has high quality.
[0051] Example 3
[0052] 1) Weigh 0.015 mol potassium carbonate (K2CO3), 0.035 mol strontium oxalate (SrC2O4), 0.09 mol aluminum acetylacetonate (AlC 15 H 21 O6) and 0.11 mol triethylborane (C6H 15 B), and grind and mix uniformly, and the purity of all raw materials is greater than 4N (i.e. 99.99%);
[0053] 2) Take the following solvents and mix them well for later use: 3.5% acetic acid solution: 20 mL, ethanol: 40 mL, deionized water: 20 mL;
[0054] 3) Add the weighed raw materials into the prepared solvent in sequence, heat to 80° C. and keep stirring for 30 minutes until a uniform suspension solution is formed;
[0055] 4) Transfer the obtained suspension solution to a 150 mL hydrothermal reactor, seal it and place it in a heating device, set the reaction temperature to 200°C. Keep the reaction at this temperature for 52 hours. Slowly cool it to 100°C according to the predetermined cooling program, and control the cooling rate at 0.7°C / h;
[0056] 5) After the reactor is cooled to room temperature, open and take out the reaction product. Remove the residual solvent and impurities by filtering, and wash the product with deionized water for 3 times. Finally, dry the product at 80°C for 12 hours to obtain the target crystal KSrAl3B2O9.
[0057] Figure 1 -(3) shows the crystal grown in Example 3. The crystal size is 5 mm. The crystal is opaque and its quality is slightly worse than that of the crystals prepared in Examples 1 and 2.
[0058] Example 4: XRD test
[0059] Using a Cu Kα irradiation The powder X-ray diffraction measurement of KSrAl3B2O9 crystal obtained in Example 2 was carried out using a Rigaku SmartLab9kW diffractometer with a diffraction monochromator. The experimental data were collected at ambient temperature in the 2θ range of 10° to 70°, with a step size of 0.01° and a step length of 2 seconds. The results are shown in Figure 2 shown.
[0060] The rocking curve test was carried out using a D5005 high-resolution X-ray diffractometer produced by Bruker-axs of Germany, which was equipped with a CuK α1 The target source (λ=1.5405A), the tube voltage is set to 30kV, and the tube current is 30mA. Process the a-direction crystal and ensure that the crystal is polished on both sides. Figure 3 The rocking curve of the KSrAl3B2O9 crystal obtained in Example 2 is shown. It can be observed from the figure that the half-peak width of the KSrAl3B2O9 crystal is only 312.5 arc seconds, and the diffraction peak is relatively narrow, which indicates that the lattice integrity of the crystal is very good.
[0061] Example 5: Transmission spectrum test:
[0062] At room temperature, we used a Hitachi UH4150 spectrophotometer to conduct a detailed UV-visible-near infrared diffuse reflectance spectrum measurement of the KSrAl3B2O9 material obtained in Example 2, with a wavelength range of 190 nanometers to 2000 nanometers. As shown in Figure X, the UV cutoff boundary of KSrAl3B2O9 is clearly located below 200 nanometers, and it exhibits a transmission efficiency of about 25% at a wavelength of 200 nanometers.
[0063] Example 6: Birefringence Characteristics Test
[0064] Furthermore, within the visible light wavelength range, we used a Nikon Eclipse E200MV POL polarization microscope to accurately experimentally measure the birefringence properties of the KSrAl3B2O9 crystal obtained in Example 2, and the measurement results are shown in Figure x. Under the irradiation of a visible light source, the birefringence value of KSrAl3B2O9 was accurately measured to be 0.026, which is consistent with the data reported in existing literature, verifying the stability and consistency of its birefringence characteristics.
Claims
1. A method for growing KSrAl3B2O9 crystals, characterized in that: The specific steps include: Step 1: Weigh potassium carbonate, strontium oxalate, aluminum acetylacetonate and triethylboron in a molar ratio of potassium carbonate: strontium oxalate: aluminum acetylacetonate: triethylboron = 0.015: 0.025-0.035: 0.08-0.10: 0.07-0.11; Step 2: Measure acetic acid solution, ethanol, and deionized water, mix them evenly and set aside, the volume ratio is acetic acid solution: ethanol: deionized water = 1:2:1, wherein the molar volume ratio (mol:ml) of potassium carbonate and acetic acid solution is 0.015:20; Step 3: Add the raw materials weighed in step 1 to the solvent prepared in step 2, heat to 70-90° C. and stir to form a suspension solution; Step 4: Transfer the solution obtained in step 3 to a hydrothermal reactor, seal it, and keep it at 190-210°C for 36-52 hours, then cool it to 90-110°C; Step 5: After the reaction is completed, take out the reactor and cool it to room temperature, open the reactor, filter, wash and dry the reaction product to obtain the target crystal KSrAl3B2O9.
2. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: The purity of the raw materials potassium carbonate, strontium oxalate, aluminum acetylacetonate and triethyl boron is greater than 4N.
3. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: In the step 2, a 3.5% acetic acid solution is used.
4. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: The stirring time in step 3 is 20-40 minutes.
5. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: The cooling rate in step 4 is 0.3-0.7°C / h.
6. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: In the step 5, the drying temperature is 65-90° C. and the drying time is 10-13 hours.
7. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: In the step 1, the molar ratio is potassium carbonate: strontium oxalate: aluminum acetylacetonate: triethylboron = 0.015: 0.03: 0.09: 0.
09.
8. The method for growing KSrAl3B2O9 crystals according to claim 1, characterized in that: The specific steps include: Step 1: weigh 0.015 mol potassium carbonate, 0.03 mol strontium oxalate, 0.09 mol aluminum acetylacetonate and 0.09 mol triethylboron, the purity of all raw materials being greater than 4N; Step 2: Measure 20 mL of 3.5% acetic acid solution, 40 mL of anhydrous ethanol, and 20 mL of deionized water and mix them evenly for later use; Step 3: Add the raw materials weighed in step 1 to the solvent prepared in step 2, heat to 80°C and continue stirring for 30 minutes to form a suspension solution; Step 4: Transfer the solution obtained in step 3 to a 150 mL hydrothermal reactor, seal it and keep it at 200°C for 44 hours, then slowly cool it to 100°C, and maintain the cooling rate at 0.5°C / h; Step 5: After the reaction is completed, the reactor is taken out and cooled to room temperature, the reactor is opened, the reaction product is filtered, and washed with deionized water three times to remove residual solvent and impurities, and then dried at 80°C for 12 hours to obtain the target crystal KSrAl3B2O9.
9. KSrAl3B2O9 crystal obtained by the growth method according to any one of claims 1 to 8.
10. Use of the KSrAl3B2O9 crystal according to claim 9 in the field of ultraviolet birefringence optics.